The safety and tolerance of phytotherapies in menopausal medicine – a review of the literature - Czuczwar, Piotr; Paszkowski, Tomasz; Lisiecki, Marek; Woźniak, Sławomir; Stępniak, Anna (Menopause Review/Przegląd Menopauzalny, 2017)
Phytoestrogens are polyphenol, non-steroidal substances of plant origin, resembling 17-estradiol in structure. These substances can act as either agonists or antagonists of oestrogen receptors  and . Phytoestrogens are widely used to alleviate menopausal symptoms, such as hot flushes and night sweats. Most of the currently available products of plant origin registered to soften climacteric symptoms consist of extracts obtained from soy, red clover, or black cohosh. Non-hormonal phytotherapy is a new alternative for patients suffering from menopausal symptoms. Active ingredients such as PI 82-GC FEM extract do not show any direct hormonal mechanisms of action typical for oestrogens and phytoestrogens. There are concerns about the safety and tolerability of phytoestrogens. In this review we summarise the current literature regarding the clinical aspect of safety and tolerance of different phytotherapies used to relieve menopausal symptoms.